PERBEDAAN USIA, PENDIDIKAN DAN PEKERJAAN IBU YANG MEMILIKI ANAK BALITA DENGAN PERILAKU KUNJUNGAN IBU KE POSYANDU DI RW 17 DESA CILEUNGSI KECAMATAN CILEUNGSI KABUPATEN BOGOR - Wahyuni, Nita Tri; Herselowati, Herselowati; Pawestri, Nui; Septiani, Yuhana; Puspitasari, Risma Ananda (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Posyandu is a public health service effort that has the main priority of accelerating the reduction in maternal and child mortality rates. A visit from a toddler's mother is very important for toddlers. There are several impacts experienced by toddlers if they are not active in posyandu activities. The aim of this research is the difference in age, education and occupation of mothers who have children under five with the behavior of mothers visiting posyandu in RW 17 Cileungsi Village, Cileungsi District, Bogor Regency in 2024. This research is a quantitative analytical research using a cross sectional study time approach carried out in RW 17 Cileungsi Village, Cileungsi District, Bogor Regency in December 2024. The sample in this study was 60 respondents. The research instrument uses primary data, namely interviews and questionnaires. The results of the research show that there are differences in education and employment of mothers who have children under five and visits to the posyandu, respectively, the chisquare test value is p value = 0.012, p value = 0.005 (p < 0.05). On the other hand, there was no difference in the age of mothers who had toddlers and visits to posyandu, with a chi-square test value of p value = 0.871 (p > 0.05). This shows that increasing awareness through education and work is very important to encourage mothers to take toddlers to posyandu